Therapeutic potential of anthocyanin-rich roselle extract as anti-obesity agent - Ismail, Rabiatul Adawiyah (Universiti Sains Malaysia, 2016)
Obesity is a chronic disease of multifactorial origin and can be defined as an increase accumulation of fat in adipose tissue. Besides its roles in triglycerides storage, adipose tissue also responsible for secretion of certain types of adipokines. There is an association between adipokines with oxidative stress in relation to obesity. Roselle or scientifically known as Hibiscus sabdariffa Linn belongs to Malvaceae family which cultivating worldwide and consumed as beverages, flavoring agent, and herbal medicine. Anthocyanin is one of the phytochemicals present in roselie which act as an antioxidant. Roselle has been claimed traditionally to reduce obesity through its antioxidant properties. The aim of this study was to investigate the effect anthocyanin-rich roselie extracts on obesity. The parameters studied include body mass index (BMI), histopathological of liver and aorta and oxidative stress assessment. Twenty-eight (n=28) Sprague-Dawley rats were divided into 5 groups. Group 1 served as negative control, normal rat. The remaining 4 groups fed with commercial High-Fat diet (HFD) for 6 weeks to induce obesity in the rat. Group 2 designated as positive control obese-rat without treatment, Group 3 obese-rat, treated with 300 mg/kg Roselle aqueous +1% TFA extract, Group 4 obese-rat treated with 300 mg/kg Roselle ethanol +1% TFA and Group 5 obese-rat treated with 20 mg/kg vitamin C. The intervention period was 3 weeks. BMI was measured weekly. Rats were euthanized at the end of the study. The serum levels of oxidative stress markers (superoxide dismutase/SOD and glutathione reductase/GR) were assessed. While the liver and descending thoracic aorta were subjected for histopathological studies using hematoxylin and eosin staining (H&E stain) and scanning electron microscope (SEM). Three-weeks of treatment significantly reduced BMI in all treated group. Roselle aqueous + 1% TFA significantly improved histopathological changes in liver and thoracic aorta as compared to other treatments. However, there were no changes in antioxidant markers in all study groups. These results demonstrated roselie aqueous + 1% TFA is a potential treatment for obesity.